(untitled) - Ogura, Takekazu (Tokyo, 1970)
This book was produced in Japanese, and translated into excellent English, as a Japanese contribution to the FAO Freedom from Hunger Campaign. It is a comprehensive account (with numerous tables and graphs) of agricultural development in Japan from the Meiji Restoration (1868) to 1963.
Keywords: Nông nghiệp,Agriculture; Khía cạnh kinh tế,Economic aspects; Nhật Bản,Japan